Sonographic landmarks in hamstring muscles - Balius, Ramon (Skeletal Radiol, 2019)
The ultrasound examination of hamstrings inspires respect due to the connective complexity of their structures, particularly for sonographers who are not used to this kind of study. Therefore, it is important to know the specific ultrasound reference points that facilitate the location of the hamstring structures, dividing them into four areas of interest: (a) tendinous origin of the hamstring, (b) the proximal half, (c) distal and medial half, and (d) distal and lateral half. The origin of the hamstrings is found at the level of the ischial tuberosity. Here, the connective structures under study are the common tendon and the semimembranosus tendon, together with the muscle fibers more proximal to the semitendinosus, which can also be assessed through ultrasound locating the ischial tuberosity. The proximal half of the thigh consists of a characteristic structure made up by the common tendon, the sciatic nerve and the semimembranosus tendon, enabling to define the biceps femoris and the semitendinosus, respectively. To identify the distal and medial section, the volumetric relationship between the ST and SM muscle masses is used, where it is also possible to identify the three muscles in the knee that make up the pes anserine. To identify the distal and lateral sections, the sciatic nerve pathway is followed until identifying both heads of the biceps femoris. These four areas of interest, with their specific landmarks, show a tuning fork that enables the comprehensive study of hamstrings through ultrasound. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00256-019-03208-x) contains supplementary material, which is available to authorized users.